An iterative algorithm for the generalized centro-symmetric solution of the generalized coupled Sylvester matrix equations AV+BW=EVF+C, MV+NW=GVH+D. (2022) - Ramadan, Mohamed A.; El-Sharway, Marwa H.; El-Shazly, Naglaa M.
No abstract available